BLIND LOYALITY PENGGUNA iPhone - Ni Luh Putu Inten Rumini; I Gede Ketut Sri Budarsa (Forum Manajemen, 2017)
This study aimed to analyze the existence of Blind Loyalty among iPhone users among students Politeknik Negeri Bali, the research team used qualitative research methods in which a team of researchers tried to collect as much as possible the main reasons were the cause of the Blind Loyalty. In this study, the data we use is data taken directly or primary data collected using data collection techniques interview later interviews conducted as necessary so that the team can no longer find the reasons for Blind Loyalty or reasons a team of researchers have repeatedly found. The respondents of this study were male and female students in Politeknik Negeri Bali campus environment where the research team will be specific to the students of the iPhone in Business Administration majoring in environmental Politeknik Negeri Bali. Respondents were the source of our data is the iPhone users of all types and has been using the iPhone for 1 (one) year or more.